Ion recombination correction factor in scanned light-ion beams for absolute dose measurement using plane-parallel ionisation chambers - Rossomme, Severine; Horn, Julian; Brons, Stephan; Jäkel, Oliver; Mairani, Andrea (Physics in medicine and biology, 2017)
Based on international reference dosimetry protocols for light-ion beams, a correction factor ( k s ) has to be applied to the response of a plane-parallel ionisation chamber, to account for recombination of negative and positive charges in its air cavity before these charges can be collected on the electrodes. In this work, k s for IBA PPC40 Roos-type chambers is investigated in four scanned light-ion beams (proton, helium, carbon and oxygen). To take into account the high dose-rates used with scanned beams and LET-values, experimental results are compared to a model combining two theories. One theory, developed by Jaffé, describes the variation of k s with the ionization density within the ion track (initial recombination) and the other theory, developed by Boag, describes the variation of k s with the dose rate (volume recombination). Excellent agreement is found between experimental and theoretical k s -values. All results confirm that k s cannot be neglected. The solution to minimise k s is to use the ionisation chamber at high voltage. However, one must be aware that charge multiplication may complicate the interpretation of the measurement. For the chamber tested, it was found that a voltage of 300 V can be used without further complication. As the initial recombination has a logarithmic variation as a function of 1/ V , the two-voltage method is not applicable to these scanned beams.
Gesehen am 25.04.2018